ON THE EXISTENCE OF OPTIMAL CONTROL FOR STOCHASTIC DIFFERENTIAL FUNCTIONAL EQUATIONS UNDER THE INFLUENCE OF EXTERNAL DISTURBANCES. I. COMPARISON THEOREM - Юрченко, Ігор (SWorldJournal, 2025)
The article discusses the comparison theorem for solutions of stochastic differential functional equations under the influence of external disturbances and its application to one problem of stochastic control.